Chemoprophylaxis for venous thromboembolism in pelvic and/or acetabular fractures: A systematic review. Issue 4 (April 2022) - Shu, Henry T.; Yu, Andrew T.; Lim, Philip K.; Scolaro, John A.; Shafiq, Babar
Highlights: Compared with UH, LMWH was associated with lower odds of VTE and death. DOACs were associated with lower risk of DVT compared with LMWH. Early VTE chemoprophylaxis was better than late administration in terms of VTE and death. Many patients with acetabular fractures are underdosed with LMWH, with inadequate aFXa levels. Abstract: Background: It is unclear which pharmacological agents, and at what dosage and timing, are most effective for venous thromboembolism (VTE) prophylaxis in patients with pelvic/acetabular fractures. Methods: We searched the Cochrane Database of Systematic Reviews, Embase, Web of Science, EBSCO, and PubMed on October 3, 2020, for English-language studies of VTE prophylaxis in patients with pelvic/acetabular fractures. We applied no date limits. We included studies that compared efficacy of pharmacological agents for VTE prophylaxis, timing of administration of such agents, and/or dosage of such agents. We recorded interventions, sample sizes, and VTE incidence, including deep vein thrombosis (DVT) and pulmonary embolism. Results: Two studies (3604 patients) compared pharmacological agents, reporting that patients who received direct oral anticoagulants (DOACs) were less likely to develop DVT than those who received low molecular weight heparin (LMWH) (p < 0.01). Compared with unfractionated heparin (UH), LMWH was associated with lower odds of VTE (odds ratio [OR] = 0.37, 95% confidence interval [CI]: 0.22–0.63) and death (OR = 0.27, 95% CI: 0.10–0.72). Three studies (3107 patients) compared timing of VTE prophylaxis, reporting that late prophylaxis was associated with higher odds of VTE (OR = 1.9, 95% CI: 1.2–3.2) and death (OR = 4.0, 95% CI: 1.5–11) and higher rates of symptomatic DVT (9.2% vs. 2.5%, p  = 0.03; and 22% vs. 3.1%, p  = 0.01). One study (31 patients) investigated dosage of VTE prophylaxis, reporting that a higher proportion of patients with acetabular fractures were underdosed (23% of patients below range of anti–Factor Xa [aFXa] had acetabular fractures vs. 4.8% of patients within adequate range of aFXa, p <0.01). Conclusions: : Early VTE chemoprophylaxis (within 24 or 48 h after injury) was better than late administration in terms of VTE and death. Many patients with acetabular fractures are underdosed with LMWH, with inadequate aFXa levels. Compared with UH, LMWH was associated with lower odds of VTE and death. DOACs were associated with lower risk of DVT compared with LMWH. Level of Evidence: : III, systematic review of retrospective cohort studies.